Exposure route mediates toxicological effects of sulphur and fluxapyroxad fungicides in a non-target butterfly - Mine Yilmazer; Marie Bakenecker; Roland Busch; Farina Fuchs; Anna Hitzler; Klaus Fischer (PLoS ONE, 2026)
Agricultural intensification and the associated increase in pesticide use have raised concerns about impacts on non-target insects. However, fungicides, despite their frequent application, remain poorly studied, particularly for herbivorous species. This is partly caused by the fact that they are considered less harmful than other pesticides. We here investigate the effects of three fungicides commonly used in viticulture, two sulphur- and one fluxapyroxad-based ones, on the cabbage white butterfly ( Pieris rapae ) under controlled laboratory conditions. Larvae were exposed to fungicides orally via treated host plants or by direct contact, and mortality and sublethal effects were assessed during development. In our study, oral exposure did not increase mortality relative to controls. Regarding sublethal effects, larvae exposed orally to sulphur-based fungicides exhibited a longer pupal development compared to controls. Additionally, larvae exposed to fluxapyroxad showed shorter development time and higher fat content than those exposed to sulphur-based fungicides. Contact exposure resulted in increased mortality relative to controls, with no significant differences among fungicides. These findings demonstrate that fungicide effects on non-target Lepidoptera are route-dependent, resulting in sublethal impacts via ingestion and lethal effects via contact exposure. Our results thus emphasize the need to consider (1) the dual risk posed by fungicides through both lethal and sublethal effects, (2) exposure route, and (3) fungicide-specific responses when assessing fungicide risks, particularly in agricultural systems where non-target Lepidoptera may occur. Detrimental effects of direct contact can be minimized through the timing of fungicide applications, thereby reducing the route-dependent risks identified in this study.